DEVELOPMENT OF CRISPY VEGETABLE CHIP FROM KALE - Rithmanee, Thanyanun (PSRU Journal of Science and Technology, 2024)
This research aimed to develop crispy vegetable chips from kale product and studied the physical, chemical, microbiological properties and sensory evaluation to obtain a good quality product. The product of crispy vegetable chip from kale for two recipes were evaluated with the color value (L*, a*, b*), water activity (aw), moisture content, nutritional value, total plate count, yeast and mold and consumer preference test. From the experimental result, it was found that L*, a*, aw, moisture content, nutritional value of recipe No.1 and recipe No.2 of crispy vegetable chip from kale were increased significantly different (P≤0.05). However, the b* value was not significantly different (P˃0.05). The analysis of the total plate count and yeast and mold of the product of recipe No.1 has been compliant according to Thai community product standard of dried seaweed (TISI 515/2547). The product of crispy vegetable chip from kale with recipe No.1 differentiates from recipe No.2 by using sesame oil and soy sauce as ingredients has the highest score from panelists for every sensory attribute with moderately from sensory evaluation test. Therefore, recipe No.1 of crispy vegetable chips from kale is a suitable solution for transferring knowledge to Ban Suan Ngok Ngam community enterprise, Nan province to make the product to be a commercial distribution in the future.